Laminated Ti (C, N)-based metal ceramic and preparation method thereof

Through the laminated structure and temperature increase rate control method, the problem of insufficient strength and toughness of Ti(C,N)-based ceramics is solved, and the surface hardness and core toughness are improved, which is extended. The service life of cutting tools and reduces production costs.

CN119194149APending Publication Date: 2024-12-27HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411225880.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the processing process, Ti(C,N)-based ceramics are prone to microcracks in the material due to insufficient strength and toughness, which limits its wide application in the field of cutting tools. The existing super hard coatings are expensive to prepare and are easy to fall off. Impacts service life.

Method used

Using the Ti(C,N)-based ceramic preparation method with a laminated structure, the liquid phase sintering of molybdenum carbide and nanotungsten carbide is promoted to form a (W,Mo,Ti)(C,N) ring shape by controlling the heating rate and heating current. Phase, combined with multi-walled carbon nanotubes, the fracture toughness of the core is improved, and stress concentration between layers is reduced through A-B-A three-layer assembly.

Benefits of technology

The surface hardness and core toughness of Ti(C,N)-based ceramics are improved, which prevents cracks from spreading during cutting, reduces production costs and improves service efficiency and life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194149A_ABST
    Figure CN119194149A_ABST
Patent Text Reader

Abstract

The invention discloses laminated Ti (C, N)-based metal ceramic and a preparation method thereof, and relates to the field of powder metallurgy, the preparation method comprises the following steps: S1, mixing titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide, hard alloy balls and absolute ethyl alcohol, and drying to obtain a mixture A; mixing titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide, multi-walled carbon nanotubes, hard alloy balls and absolute ethyl alcohol, and drying to obtain a mixture B; s2, adding the mixture A and the mixture B into a mold layer by layer to obtain an A-B-A three-layer mixture, and performing spark plasma sintering to obtain laminated Ti (C, N)-based metal ceramic; spark plasma sintering is carried out under the vacuum condition, the heating rate is 50-75 DEG C / min, the temperature is increased to 1350-1500 DEG C for heat preservation sintering, the heating current during heat preservation sintering is 1700-2000 A, the sintering pressure is 25-40 Mpa, and the heat preservation sintering time is 8-20 min. The surface of the Ti (C, N)-based metal ceramic prepared through the method has high hardness so that high-speed cutting can be facilitated, and the core has high toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of powder metallurgy, in particular to a laminated Ti (C, N)-based cermet and a preparation method thereof. Background Art

[0002] Ti(C,N)-based cermet is a composite material with a ceramic hard phase and a metal binder phase. It has both the plastic toughness of metal and the wear resistance of ceramic. It has received considerable research attention in the field of cutting tools due to its excellent wear resistance, low friction coefficient and extraordinary chemical stability.

[0003] Ti(C,N)-based cermets have the advantages of high hot hardness, good wear resistance, low friction coefficient, and good chemical stability. Therefore, they are often considered as substitutes for WC-based cemented carbide (such as WC-Co cemented carbide). However, the strength and toughness of Ti(C,N)-based ceramics are lower than those of WC-Co. The lower strength and toughness make it easy for microcracks to form inside the material during processing, thereby reducing its service life and hindering its widespread application. For example, when Ti(C,N)-based ceramics are used as cutting tools, they need to have both good strength and fracture toughness.

[0004] Adding multi-walled carbon nanotubes for nano-toughening is a common method to improve toughness. Multi-walled carbon nanotubes can improve the strength and toughness of metal ceramics, but multi-walled carbon nanotubes will promote the formation of annular phases. Too many annular phases increase the hardness of the material, and the toughness and strength are reduced. Therefore, it is not easy to achieve high hardness and good fracture toughness at the same time.

[0005] The prior art discloses a method for preparing a superhard coating on the surface of a Ti(C,N)-based cermet cutting tool by PVD, CVD, etc., which can increase the surface hardness and wear resistance of the Ti(C,N)-based cermet cutting tool while maintaining good strength, thereby greatly improving its use efficiency and life. However, the preparation of the coating is relatively expensive, and there is an obvious interface between the coating and the substrate. The coating may fall off during the use of the tool and lose its effect, limiting its industrial application. Summary of the invention

[0006] The present invention aims to provide a laminated Ti(C,N)-based cermet and a preparation method thereof, so that the Ti(C,N)-based cermet has a higher surface hardness for high-speed cutting and a higher core toughness to prevent crack propagation caused by wear during the cutting process.

[0007] In order to solve the above technical problems, the specific solution adopted by the present invention is: a method for preparing a laminated Ti (C, N)-based cermet, comprising the following steps:

[0008] S1: mixing titanium carbonitride, tungsten carbide, cobalt and molybdenum carbide to obtain powder A, mixing powder A with cemented carbide balls and anhydrous ethanol, and drying to obtain mixed material A;

[0009] Mix titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes to obtain powder B, mix powder B with cemented carbide balls and anhydrous ethanol, and dry to obtain mixed material B;

[0010] S2: adding the mixture A and the mixture B into the mold layer by layer to obtain the ABA three-layer mixture, and performing spark plasma sintering to obtain the laminated Ti(C,N)-based cermet;

[0011] The heating rate of spark plasma sintering is 50-75°C / min, the temperature is raised to 1350-1500°C for heat preservation sintering, the heating current during heat preservation sintering is 1700-2000A, the sintering pressure is 25-40Mpa, and the heat preservation sintering time is 8-20min.

[0012] As a further optimization of the above technical solution: the thickness ratio of the ABA three-layer mixture is 1.2-1.3:3:1.2-1.25.

[0013] As a further optimization of the above technical solution: the thickness of the mixture A layer on both sides of the ABA three-layer mixture is different.

[0014] As a further optimization of the above technical solution: according to mass percentage, powder A is composed of 64.6-65% titanium carbonitride, 21.5-23.5% tungsten carbide, 7.5-9.2% cobalt and 3.5-4.5% molybdenum carbide, and powder B is composed of 64.6%-65% titanium carbonitride, 21.5-23.5% tungsten carbide, 7.5-9.2% cobalt, 3.5-4.5% molybdenum carbide and 0.34-0.43% multi-walled carbon nanotubes.

[0015] As a further optimization of the above technical solution: in step S1, powder A, carbide balls and anhydrous ethanol are mixed in a weight volume ratio of 1g:8g:1ml and dried to obtain a mixture A; powder B, carbide balls and anhydrous ethanol are mixed in a weight volume ratio of 1g:8g:1ml and dried to obtain a mixture B.

[0016] As a further optimization of the above technical solution: in step S1, powder A and powder B are respectively mixed with carbide balls and anhydrous ethanol by planetary ball milling or drum ball milling, and the mixing time is 20-24 hours.

[0017] As a further optimization of the above technical solution: in step S1, the drying temperature is 60-70°C and the drying time is 12-16h.

[0018] As a further optimization of the above technical solution: the heating rate of spark plasma sintering is as follows: the heating rate below 800°C is 50°C / min, the heating rate from 800°C to 1100°C is 75°C / min, and the heating rate above 1100°C is 70°C / min; the heating current during the heating process is less than 3000A.

[0019] As a further optimization of the above technical solution: the vacuum condition during spark plasma sintering is ≤1×10 -1 Pa.

[0020] A laminated Ti(C,N)-based metal ceramic is prepared by any of the above preparation methods.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention promotes the liquid phase sintering of molybdenum carbide and nano-tungsten carbide by controlling the heating rate and heating current. Molybdenum carbide and nano-tungsten carbide will become free molybdenum ions and tungsten ions during the liquid phase sintering process. By controlling the size of the heating current, appropriate plasma can be generated to promote the dissolution of molybdenum ions and tungsten ions to form (W, Mo, Ti) (C, N) annular phases, inhibit the growth of Ti (C, N) grains, and improve the surface hardness;

[0023] The ABA three-layer stacking assembly method can effectively reduce the stress concentration between layers, but the design of the stacking structure will cause each layer to be heated unevenly during the heating process when using a sintering furnace that applies current in one direction for heating. Combined with the heating rate and heating current conditions of the present invention, the ABA three-layer mixture can be heated evenly during spark plasma sintering, and the grains can grow evenly.

[0024] Adding multi-walled carbon nanotubes to the core can improve the bonding strength between layers, improve the bonding between interfaces, make the layers more tightly bonded, and at the same time promote the dissolution of molybdenum ions and tungsten ions to form more (W,Mo,Ti)(C,N) annular phases, and then combine their own bridging and pull-out properties to jointly improve the fracture toughness of the core, so that the surface of the Ti(C,N)-based metal ceramic prepared by the present invention has a higher hardness for high-speed cutting, and the core has a higher toughness to prevent the propagation of cracks caused by wear during the cutting process.

[0025] 2. The present invention effectively suppresses the growth of Ti(C,N) grains by controlling the heating rate and the heating current, thereby improving production efficiency and reducing production costs with a more energy-saving and efficient process. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1The powder loading method of groups A and B in Example 1, Example 2 and Example 3;

[0027] Figure 2 This is a 30,000-fold scanning electron microscope image of the surface of the laminated Ti(C,N)-based cermet in Example 3;

[0028] Figure 3 This is a scanning electron microscope image of the cross section of the laminated Ti(C,N)-based metal ceramic in Example 3 at 30,000 times magnification. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts of the present invention that are not described and disclosed in detail in the following embodiments should be understood as the prior art known or should be known to those skilled in the art.

[0030] The present invention discloses a method for preparing a laminated Ti(C,N)-based cermet, comprising the following steps:

[0031] S1: titanium carbonitride, tungsten carbide, cobalt and molybdenum carbide are mixed to obtain powder A, powder A is mixed with cemented carbide balls and anhydrous ethanol, and dried to obtain mixture A; titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes are mixed to obtain powder B, powder B is mixed with YG8 cemented carbide balls and anhydrous ethanol, and dried to obtain mixture B.

[0032] Specifically, according to mass percentage, powder A is composed of 64.6-65% titanium carbonitride, 21.5-23.5% tungsten carbide, 7.5-9.2% cobalt and 3.5-4.5% molybdenum carbide, and powder B is composed of 64.6%-65% titanium carbonitride, 21.5-23.5% tungsten carbide, 7.5-9.2% cobalt, 3.5-4.5% molybdenum carbide and 0.34-0.43% multi-walled carbon nanotubes; the raw material sizes of powder A and powder B are 0.62 μm of titanium carbonitride, 200 nm of tungsten carbide, 50 nm of cobalt, 1-3 μm of molybdenum carbide, and 0.5-2 μm of multi-walled carbon nanotubes;

[0033] Mix powder A, carbide balls and anhydrous ethanol in a weight-volume ratio of 1 g:8 g:1 ml by planetary ball milling or drum ball milling for 20-24 hours, then transfer to a drying oven and dry at 60-70°C for 12-16 hours to obtain mixed material A;

[0034] Mix powder B, carbide balls and anhydrous ethanol in a weight-volume ratio of 1 g:8 g:1 ml by planetary ball milling or drum ball milling for 20-24 hours, then transfer to a drying oven and dry at 60-70°C for 12-16 hours to obtain mixed material B;

[0035] During the preparation of mixture A and mixture B, the cemented carbide balls used were both YG8 cemented carbide balls.

[0036] S2: adding mixed material A and mixed material B layer by layer into a graphite mold, and flattening the powder with a powder tablet press to obtain an ABA three-layer mixed material, and performing spark plasma sintering to obtain the laminated Ti(C,N)-based cermet;

[0037] The ABA three-layer mixture includes a mixture B layer in the middle and mixture A layers on both sides. The mixture is placed layer by layer using an asymmetric structure, and the thickness of the mixture A layers on both sides of the mixture B layer is different. This asymmetric structure of the material placement method can make the performance of the two sides of the ABA three-layer mixture close to the same within the error range. This is because during the spark plasma sintering process, the current is applied perpendicular to the surface of the material, and the thicker layer is placed on the top surface and the thinner layer is placed on the bottom surface. The top surface is in contact with more current than the bottom surface, so the top surface is designed to be thicker.

[0038] In the ABA three-layer mixture, the thickness ratio of the A-layer mixture layer, the B-layer mixture layer and the A-layer mixture layer is 1.2-1.3:3:1.2-1.25;

[0039] Spark plasma sintering is carried out under vacuum conditions (vacuum degree ≤ 1×10 -1 Pa), the heating rate of spark plasma sintering is 50-75°C / min, the heating current is less than 3000A during the heating process, the temperature is raised to 1350-1500°C for heat preservation sintering, the heating current during heat preservation sintering is 1700-2000A, the sintering pressure is 25-40Mpa, and the heat preservation sintering time is 8-20min.

[0040] It should be noted that the heating current during the heating process is less than 3000A, which means that the maximum heating current during the heating process is less than 3000A. The current loading will increase with the increase in temperature, and it is a continuous increasing process. This is common knowledge in the field. Therefore, the heating current during the heating process can be limited to a maximum value, which can ensure both stable heating and safety.

[0041] The ABA three-layer stacking assembly method can effectively reduce the stress concentration between layers. However, there is a problem in the design of the stacking structure. When using a sintering furnace that applies current unidirectionally for heating, each layer is heated unevenly during the heating process. The uneven heating will cause a large difference in the mechanical properties of the two surfaces. Therefore, a large number of layers cannot be set. In order to solve the problem of uniform heating while allowing the grains to grow evenly, the heating current and heating rate of this scheme are set, especially the heating current and heating rate after 800°C need to be controlled well.

[0042] The present invention adopts an ABA three-layer stacking assembly method, and multi-walled carbon nanotubes are added to the core mixture, which can improve the bonding strength between layers, improve the bonding between interfaces, make the layers more tightly bonded, and promote the dissolution of molybdenum ions and tungsten ions to form more (W, Mo, Ti) (C, N) annular phases. The annular phases can improve the mechanical properties of metal ceramics, and the increase of the annular phases can more significantly improve the toughness. Combined with the bridging and pull-out properties of the multi-walled carbon nanotubes themselves, the fracture toughness of the core is improved together; and for the surface mixture, the liquid phase sintering of molybdenum carbide and nano-tungsten carbide is promoted by controlling the heating rate and the heating current. The molybdenum carbide and nano-tungsten carbide will become free molybdenum ions and tungsten ions in the liquid phase sintering process. The size of the heating current can be controlled to generate appropriate plasma to promote the dissolution of molybdenum ions and tungsten ions to form (W, Mo, Ti) (C, N) annular phases, inhibit the growth of Ti (C, N) grains, and improve the surface hardness.

[0043] The present invention adopts an ABA three-layer stacking method, selects a mixture of different components in the three-layer stacking, and cooperates with a specific heating current and a heating rate, so that the surface of the Ti(C, N)-based metal ceramic prepared by the present invention has a higher hardness to facilitate high-speed cutting, and the core has a higher toughness to prevent the propagation of cracks caused by wear during the cutting process.

[0044] Example 1

[0045] (1) Preparation of Mixture A

[0046] Titanium carbonitride, tungsten carbide, cobalt and molybdenum carbide are weighed and mixed in proportion to form powder A, wherein the mass percentage of each component in powder A is 65% titanium carbonitride, 23% tungsten carbide, 8% cobalt and 4% molybdenum carbide;

[0047] 30g of powder A, 240g of YG8 hard alloy ball and 30ml of anhydrous ethanol were placed in a hard alloy ball mill and mixed for 20h, dried in a drying oven at 65℃ for 16h, and the dried mixture was put into a sealed bag and marked as mixture A;

[0048] (2) Preparation of Mixture B

[0049] Titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes are weighed in proportion as powder B, wherein the mass percentage of each component in powder B is 64.6% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 4% molybdenum carbide and 0.4% multi-walled carbon nanotubes;

[0050] Put 30g powder B, 240g YG8 carbide ball and 30ml anhydrous ethanol into a carbide ball mill and mix for 20h. Dry it in a drying oven at 65℃ for 16h. Put the dried mixture into a sealed bag and mark it as mixture B.

[0051] (3) Add the mixtures of groups A and B into the graphite mold layer by layer in three layers according to the ABA sequence.

[0052] 1) Weigh enough mixed materials from each group according to the ABA layer thickness ratio of 1.25:3:1.2;

[0053] 2) Place the weighed mixed materials into the mold layer by layer in the order of ABA, and flatten them layer by layer using a powder tablet press. Use spark plasma sintering equipment under vacuum conditions (vacuum degree ≤ 1×10 -1 The heating rate below 800°C is 50°C / min, the heating rate above 800°C is 75°C / min, the heating current does not exceed 2800A during the heating process, the temperature is raised to 1400°C for heat preservation sintering, that is, the sintering temperature is 1400°C, the heating current during heat preservation sintering is 1750A, the sintering pressure is 35Mpa, and the heat preservation sintering time is 16min, and finally a laminated Ti(C,N)-based cermet is obtained.

[0054] After testing, the surface Vickers hardness of the laminated Ti (C, N) based cermet prepared in this embodiment is 2061.6kgf / mm2, and the fracture toughness is 10.26Mpa·m1 / 2; the core Vickers hardness is 2000.9kgf / mm2, and the fracture toughness is 11.18Mpa·m1 / 2. The average grain size of the sample surface is 0.85μm, and the grain size of the cross section is 0.95μm. There are no obvious defects and pores in the sample, and the microstructure is uniform.

[0055] Example 2

[0056] (1) Preparation of Mixture A

[0057] Titanium carbonitride, tungsten carbide, cobalt and molybdenum carbide are weighed and mixed in proportion to form powder A, wherein the mass percentage of each component in powder A is 65% titanium carbonitride, 23% tungsten carbide, 8% cobalt and 4% molybdenum carbide;

[0058] 30g of powder A, 240g of YG8 hard alloy ball and 30ml of anhydrous ethanol were placed in a hard alloy ball mill and mixed for 20h, dried in a drying oven at 65℃ for 16h, and the dried mixture was put into a sealed bag and marked as mixture A;

[0059] (2) Preparation of Mixture B

[0060] Titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes are weighed in proportion as powder B, wherein the mass percentage of each component in powder B is 64.6% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 4% molybdenum carbide and 0.4% multi-walled carbon nanotubes;

[0061] Put 30g powder B, 240g YG8 carbide ball and 30ml anhydrous ethanol into a carbide ball mill and mix for 20h. Dry it in a drying oven at 65℃ for 16h. Put the dried mixture into a sealed bag and mark it as mixture B.

[0062] (3) Add the mixtures of groups A and B into the graphite mold layer by layer in three layers according to the ABA sequence.

[0063] 1) Weigh enough mixed materials from each group according to the ABA layer thickness ratio of 1.25:3:1.2;

[0064] 2) Place the weighed mixed materials into the mold layer by layer in the order of ABA, and flatten them layer by layer using a powder tablet press. Use spark plasma sintering equipment under vacuum conditions (vacuum degree ≤ 1×10 -1 The heating rate below 800°C is 50°C / min, the heating rate above 800°C is 75°C / min, the heating current does not exceed 2800A during the heating process, and the temperature is raised to 1400°C for heat preservation sintering, that is, the sintering temperature is 1400°C, the heating current in the heat preservation sintering stage is 1800A, the sintering pressure is 35Mpa, and the heat preservation sintering time is 20min, and finally a laminated Ti(C,N)-based cermet is obtained.

[0065] After testing, the Vickers hardness of the laminated Ti (C, N)-based cermet prepared by this method is 2071.5kgf / mm2, and the fracture toughness is 8.3Mpa·m1 / 2; the Vickers hardness of the core is 1977.4kgf / mm2, and the fracture toughness is 10.4Mpa·m1 / 2. The average grain size of the sample surface is 0.64μm, and the grain size of the cross section is 0.85μm. There are no obvious defects and pores in the sample, the microstructure is uniform, and there is an obvious core-ring structure.

[0066] Example 3

[0067] (1) Preparation of Mixture A

[0068] Titanium carbonitride, tungsten carbide, cobalt and molybdenum carbide are weighed and mixed in proportion to form powder A, wherein the mass percentage of each component in powder A is 65% titanium carbonitride, 23% tungsten carbide, 8% cobalt and 4% molybdenum carbide;

[0069] 30g of powder A, 240g of YG8 hard alloy ball and 30ml of anhydrous ethanol were placed in a hard alloy ball mill and mixed for 20h, dried in a drying oven at 65℃ for 16h, and the dried mixture was put into a sealed bag and marked as mixture A;

[0070] (2) Preparation of Mixture B

[0071] Titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes are weighed and mixed in proportion to form powder B, wherein the mass percentage of each component in powder B is 64.6% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 4% molybdenum carbide and 0.4% multi-walled carbon nanotubes;

[0072] 30g of powder B, 240g of YG8 carbide ball and 30ml of anhydrous ethanol were placed in a carbide ball mill and mixed for 20h, dried in a drying oven at 65℃ for 16h, and the dried mixture was put into a sealed bag and marked as mixture B;

[0073] (3) Add the mixtures of groups A and B into the graphite mold layer by layer in three layers according to the ABA sequence.

[0074] 1) Weigh enough mixed materials from each group according to the ABA layer thickness ratio of 1.3:3:1.25;

[0075] 2) Place the weighed mixed materials into the mold layer by layer in the order of ABA, and flatten them layer by layer using a powder tablet press. Use spark plasma sintering equipment under vacuum conditions (vacuum degree ≤ 1×10 -1 The heating rate below 800°C is 50°C / min, the heating rate from 800°C to 1100°C is 75°C / min, the heating rate above 1100°C is 70°C / min, the heating current during the heating process is no more than 2600A, the temperature is raised to 1400°C for heat preservation sintering, that is, the sintering temperature is 1400°C, the heating current in the heat preservation sintering stage is 1750A, the sintering pressure is 35Mpa, and the heat preservation sintering time is 20min, and finally a laminated Ti(C,N)-based cermet is obtained.

[0076] After testing, the Vickers hardness of the laminated Ti(C,N)-based cermet surface prepared in this embodiment is 2014.5kgf / mm 2 , fracture toughness is 9.7Mpa·m 1 / 2 ; Vickers hardness of the core is 1965.1kgf / mm 2 , fracture toughness is 12.35Mpa·m 1 / 2 The average grain size of the sample surface is 0.63μm, and the grain size of the cross section is 0.75μm. The sample grains are finer, there are no obvious defects and pores, the microstructure is uniform, and there is an obvious core-ring structure.

[0077] Example 4

[0078] (1) Preparation of Mixture A

[0079] Titanium carbonitride, tungsten carbide, cobalt and molybdenum carbide are weighed and mixed in proportion to form powder A, wherein the mass percentage of each component in powder A is 64.6% titanium carbonitride, 23.4% tungsten carbide, 7.5% cobalt and 4.5% molybdenum carbide;

[0080] 30g of powder A, 240g of YG8 hard alloy ball and 30ml of anhydrous ethanol were placed in a hard alloy ball mill and mixed for 20h, dried in a drying oven at 65℃ for 16h, and the dried mixture was put into a sealed bag and marked as mixture A;

[0081] (2) Preparation of Mixture B

[0082] Titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes are weighed and mixed in proportion to form powder B, wherein the mass percentage of each component in powder B is 65% titanium carbonitride, 23% tungsten carbide, 7.5% cobalt, 4.07% molybdenum carbide and 0.43% multi-walled carbon nanotubes;

[0083] 30g of powder B, 240g of YG8 carbide ball and 30ml of anhydrous ethanol were placed in a carbide ball mill and mixed for 24h, dried in a drying oven at 70℃ for 12h, and the dried mixture was put into a sealed bag and marked as mixture B;

[0084] (3) Add the mixtures of groups A and B into the graphite mold layer by layer in three layers according to the ABA sequence.

[0085] 1) Weigh enough mixed materials from each group according to the ABA layer thickness ratio of 1.2:3:1.23;

[0086] 2) Place the weighed mixed materials into the mold layer by layer in the order of ABA, and flatten them layer by layer using a powder tablet press. Use spark plasma sintering equipment under vacuum conditions (vacuum degree ≤ 1×10 -1 The heating rate below 800°C is 50°C / min, the heating rate from 800°C to 1100°C is 75°C / min, the heating rate above 1100°C is 70°C / min, the heating current does not exceed 2400A during the heating process, and the temperature is raised to 1500°C for heat preservation sintering, that is, the sintering temperature is 1500°C, the heating current in the heat preservation sintering stage is 1700A, the sintering pressure is 25Mpa, and the heat preservation sintering time is 18min, and finally a laminated Ti(C,N)-based cermet is obtained.

[0087] Example 5

[0088] (1) Preparation of Mixture A

[0089] Titanium carbonitride, tungsten carbide, cobalt and molybdenum carbide are weighed and mixed in proportion to form powder A, wherein the mass percentage of each component in powder A is 65% titanium carbonitride, 22.5% tungsten carbide, 8.2% cobalt and 4.3% molybdenum carbide;

[0090] 30g of powder A, 240g of YG8 carbide ball and 30ml of anhydrous ethanol were placed in a carbide ball mill and mixed for 22h, dried in a drying oven at 60°C for 14h, and the dried mixture was put into a sealed bag and marked as mixture A;

[0091] (2) Preparation of Mixture B

[0092] Titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes are weighed and mixed in proportion to form powder B, wherein the mass percentage of each component in powder B is 64.6% titanium carbonitride, 22.5% tungsten carbide, 8.2% cobalt, 4.3% molybdenum carbide and 0.4% multi-walled carbon nanotubes;

[0093] 30g of powder B, 240g of YG8 carbide ball and 30ml of anhydrous ethanol were placed in a carbide ball mill and mixed for 20h, dried in a drying oven at 65℃ for 16h, and the dried mixture was put into a sealed bag and marked as mixture B;

[0094] (3) Add the mixtures of groups A and B into the graphite mold layer by layer in three layers according to the ABA sequence.

[0095] 1) Weigh enough mixed materials from each group according to the ABA layer thickness ratio of 1.3:3:1.2;

[0096] 2) The weighed mixed materials are placed into the mold layer by layer in the order of ABA, and are pressed layer by layer using a powder tablet press. Spark plasma sintering equipment is used under vacuum conditions (vacuum degree ≤ 1×10 -1 The heating rate below 800°C is 50°C / min, the heating rate from 800°C to 1100°C is 75°C / min, the heating rate above 1100°C is 70°C / min, the heating current does not exceed 2200A during the heating process, and the temperature is raised to 1350°C for heat preservation sintering, that is, the sintering temperature is 1350°C, the heating current in the heat preservation sintering stage is 2000A, the sintering pressure is 40Mpa, and the heat preservation sintering time is 8min, and finally a laminated Ti(C,N)-based cermet is obtained.

[0097] Comparative Example 1

[0098] Weigh 65% titanium carbonitride, 23% tungsten carbide, 8% cobalt and 4% molybdenum carbide in proportion as a powder, put 20g of the powder, 160g of YG8 carbide ball and 20ml of anhydrous ethanol into a carbide ball mill and mix for 24h. Dry in a drying oven at 65℃ for 24h, put the dried mixture into a graphite mold, and use a spark plasma sintering device under vacuum conditions (vacuum degree ≤1×10 -1 The heating rate is 75℃ / min, the sintering temperature is 1400℃, the sintering pressure is 25Mpa, and the holding time is 12min, and finally the Ti(C,N) based metal ceramic is obtained.

[0099] The Vickers hardness of the Ti(C,N)-based cermet prepared by this method is 2029kgf / mm 2 , fracture toughness is 9.1Mpa·m 1 / 2 The sample has fine grains and few defects.

[0100] Comparative Example 2

[0101] Weigh 64.6% titanium carbonitride, 23% tungsten carbide, 8% cobalt, 4% molybdenum carbide and 0.4% multi-walled carbon nanotubes in proportion as a powder, put 20g of the powder, 160g of YG8 carbide balls and 20ml of anhydrous ethanol into a carbide ball mill and mix for 24h. Dry in a drying oven at 65℃ for 24h, put the dried mixture into a graphite mold, and use a spark plasma sintering device under vacuum conditions (vacuum degree ≤1×10 -1 The heating rate is 80℃ / min, the sintering temperature is 1400℃, the sintering pressure is 25Mpa, and the holding time is 12min, and finally the Ti(C,N) based metal ceramic is obtained.

[0102] The Vickers hardness of the Ti(C,N)-based cermet prepared by this method is 2022kgf / mm 2 , fracture toughness is 10.5Mpa·m 1 / 2 The sample has fine grains and few defects.

[0103] Comparative Example 3

[0104] The overall steps of this comparative example are the same as those of Example 3, except that the heating current in the insulation stage is 1400A, the sintering temperature is 1400°C, the sintering pressure is 35Mpa, and the insulation time is 20min, and finally a laminated Ti(C,N)-based metal ceramic is obtained.

[0105] After testing, the Vickers hardness of the laminated Ti(C,N)-based cermet surface prepared in this embodiment is 1950kgf / mm 2, fracture toughness is 9.1Mpa·m 1 / 2 ; Vickers hardness of the core is 1890kgf / mm 2 , fracture toughness is 10.1Mpa·m 1 / 2 The average grain size on the surface of the sample is 0.77μm, and the grain size on the cross section is 0.85μm. The grain distribution of the sample is relatively uniform, and the grains are relatively large.

[0106] Comparative Example 4

[0107] The overall steps of this comparative example are the same as those of Example 3, except that the heating rate is maintained at 50°C / min throughout the whole process, the sintering temperature is 1400°C, the sintering pressure is 35Mpa, and the holding time is 20min, and finally a laminated Ti(C,N)-based metal ceramic is obtained.

[0108] After testing, the Vickers hardness of the laminated Ti(C,N)-based cermet surface prepared in this embodiment is 1940kgf / mm 2 , fracture toughness is 9.2Mpa·m 1 / 2 ; Vickers hardness of the core is 1910kgf / mm 2 , fracture toughness is 9.7Mpa·m 1 / 2 The average grain size on the surface of the sample is 0.79μm, and the grain size on the cross section is 0.82μm. The grain size on the surface and cross section of the sample is not much different, and the slow heating rate leads to abnormal grain growth.

[0109] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a laminated Ti(C,N)-based cermet, characterized in that: The following steps are involved: S1: mixing titanium carbonitride, tungsten carbide, cobalt and molybdenum carbide to obtain powder A, mixing powder A with cemented carbide balls and anhydrous ethanol, and drying to obtain mixed material A; Mix titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes to obtain powder B, mix powder B with cemented carbide balls and anhydrous ethanol, and dry to obtain mixed material B; S2: adding the mixture A and the mixture B into the mold layer by layer to obtain the ABA three-layer mixture, and performing spark plasma sintering to obtain the laminated Ti(C,N)-based cermet; Among them, spark plasma sintering is carried out under vacuum conditions, the heating rate is 50-75°C / min, the temperature is raised to 1350-1500°C for heat preservation sintering, the heating current during heat preservation sintering is 1700-2000A, the sintering pressure is 25-40Mpa, and the heat preservation sintering time is 8-20min.

2. The method for preparing a laminated Ti(C,N)-based cermet according to claim 1, characterized in that: The thickness ratio of the ABA three-layer mixture is 1.2-1.3:3:1.2-1.

25.

3. The method for preparing a laminated Ti(C,N)-based cermet according to claim 2, characterized in that: The thickness of the mixture A layer on both sides of the ABA three-layer mixture is different.

4. The method for preparing a laminated Ti(C,N)-based cermet according to claim 1, characterized in that: According to mass percentage, powder A is composed of 64.6-65% titanium carbonitride, 21.5-23.5% tungsten carbide, 7.5-9.2% cobalt and 3.5-4.5% molybdenum carbide, powder B is composed of 64.6%-65% titanium carbonitride, It is composed of 21.5-23.5% tungsten carbide, 7.5-9.2% cobalt, 3.5-4.5% molybdenum carbide and 0.34-0.43% multi-walled carbon nanotubes.

5. The method for preparing a laminated Ti(C,N)-based cermet according to claim 1, characterized in that: In step S1, powder A, carbide balls and anhydrous ethanol are mixed in a weight volume ratio of 1g:8g:1ml and dried to obtain a mixture A; powder B, carbide balls and anhydrous ethanol are mixed in a weight volume ratio of 1g:8g:1ml and dried to obtain a mixture B.

6. The method for preparing a laminated Ti(C,N)-based cermet according to claim 1, characterized in that: In step S1, powder A and powder B are respectively mixed with carbide balls and anhydrous ethanol by planetary ball milling or drum ball milling, and the mixing time is 20-24 hours.

7. The method for preparing a laminated Ti(C,N)-based cermet according to claim 1, characterized in that: In step S1, the drying temperature is 60-70°C and the drying time is 12-16 hours.

8. The method for preparing a laminated Ti(C,N)-based cermet according to claim 1, characterized in that: The heating rates of spark plasma sintering are as follows: the heating rate below 800°C is 50°C / min, the heating rate from 800°C to 1100°C is 75°C / min, and the heating rate above 1100°C is 70°C / min; the heating current during the heating process is less than 3000A.

9. The method for preparing a laminated Ti(C,N)-based cermet according to claim 1, characterized in that: The vacuum degree during spark plasma sintering is ≤1×10 -1 Pa.

10. A laminated Ti(C,N)-based cermet, characterized in that: Prepared by any preparation method in claims 1-9.

Citation Information

Cited By

  • Carbon-nitrogen dual-phase ceramic material and preparation method thereof

    CN122647232A